STRATEGI PENGUATAN PENDIDIKAN KARAKTER PADA SISWA SEKOLAH DASAR NEGERI 5 KAWAN KABUPATEN BANGLI DI MASSA PANDEMI COVID-19 - Kadek Jayanthi Riva Prathiwi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to analyze strategies for strengthening character education in students at 5 Kawan Elementary School, Bangli Regency during the Covid-19 Pandemic. This research is classified as qualitative research. Data collection methods were carried out by means of interviews, observations and reviewing school documents. The data was analyzed using the stages of data reduction, data display and data verification. Data is presented in a qualitative descriptive manner. The results of the research state that the strategy prepared by teachers and schools at SD Negeri 5 Kawan in implementing strengthening character education for students is a metacognitive strategy which emphasizes the importance of students concentrating on learning, organizing and planning learning and evaluating learning methods. So from this it is hoped that students will be able to implement strengthening the character they have. In this research, there were changes in strengthening children's character, especially in high classes during the Covid 19 pandemic. Keywords: Strengthening, Character education, Covid-19 pandemic